Effect of the Fe Nanoparticles Generated by Pulsed Plasma in Liquid in the Catalyzed Ozone Removal of Phenolphthalein - O. Olea-Mejia; M. Fernández-Mondragón; C. Barrera-Díaz; A. Cabral-Prieto (International Journal of Photoenergy)
We have synthesized, in this work, zero valent iron (ZVI) nanoparticles to improve the efficiency of degradation of phenolphthalein catalyzed by ozone in aqueous solution. The Fe nanoparticles were obtained using the pulsed plasma in liquid (PPL) method with water as the liquid medium. Such nanoparticles have a mean size of 12 nm and are composed of ~80% Fe0, while the rest are a mixture of Fe+2 and Fe+3 oxides. The degradation of phenolphthalein was carried on a glass reactor injecting a constant amount of ozone and introducing different concentrations of Fe nanoparticles to the system. When using pure ozone, the percentage of degradation of phenolphthalein measured by colorimetry after one hour of reaction was 84%. However, when Fe nanoparticles are used, such percentage can be as high as 98% in 50 minutes of reaction. Furthermore, the degradation rate constant was 0.0334 min−1 with only ozone and it can be as high as 0.0733 min−1 with Fe nanoparticles. Finally, the total mineralization of phenolphthalein was obtained by total organic carbon (TOC) determinations. It is shown that when using only ozone, we obtained a percentage of mineralization of 49% and 96% when using the highest concentration of Fe nanoparticles.